Possessive pour in the French Lexicon of the Ivory Coast and Language Contact - Akissi Boutin, Béatrice (Linguistik Online, 2007)
Any variationist study of Ivory Coast French needs to take into account sociolinguistic considerations and systemic features of other contact languages. For instance, there is a specific usage of pour against which the interference hypothesis can easily be tested: FI: Le kaki que je porte présentement, c’est pour un bachelier qui me l’a laissé avant de partir en fac, cadeau. (Lafage 2003: 676). Avant de te moquer du linge de ta voisine, regarde si pour toi est propre.. In Ivory Coast French, pour (N/Pro) can display a variety of functions: it can be part of associative predications, it can stand for genitive phrases in an anaphoric construction, make reference to an object in relation with another and participate in various idiomatic expressions. This paper has a twofold objective. First, I argue that pour (N/Pro) constructions has to be analysed as an empty headed "associative" noun phrase. Second, I will show the relevance of extra- AND intersystemic factors in accounting for language variation. Incidentally, the use of pour (N/Pro) constructions seems to be conditioned by the availability of similar constructions in other Ivory Coast languages on the one hand, such as baoule (o liε) or dioula (à tá), and, cultural needs on the other.